Effectiveness Evaluation of Optical Illusion Deceleration Markings for a V-Shaped Undersea Tunnel Based on the Set Pair Analysis Method and the Technique for Order Preference by Similarity to Ideal Solution Theory. Issue 5 (May 2023) - Pan, Fuquan; Wu, Qiudie; Wang, Zhaoqiang; Wang, Lin; Zhang, Lixia; Li, Min
To improve traffic safety in undersea tunnels, the speed control effect of optical illusion deceleration markings (OIDMs) in V-shaped undersea tunnels and their applicability to drivers were explored. In this study, UC-Win/Road software was used to build a simulation scenario, and the V-shaped Jiaozhou Bay undersea tunnel in Qingdao, China, was selected as the simulated road section. Four kinds of OIDMs were selected as the research objects. According to the physiological and psychological response characteristics of drivers to the visual recognition process of OIDMs and vehicle driving parameters, three primary and six secondary evaluation indices were identified. The analytic hierarchy process-entropy weight method was applied to assign weights to each evaluation index in combination, and a comprehensive evaluation model based on the set pair analysis method and the technique for order preference by similarity to ideal solution was constructed to comprehensively evaluate the effectiveness of the OIDMs based on the ternary coefficient and the comprehensive evaluation index. To verify the accuracy of the model, the data of the three secondary evaluation indicators with larger weight coefficients were statistically analyzed, and the results showed that the results of the statistical analysis of the data were consistent with the results of the model test. In the entrance section of the tunnel, the combination of white inverted fishbone deceleration markings and red warning pavement has the highest comprehensive evaluation index of γ A 1 = 0.9611. In the downhill section of the tunnel, the white variable-spacing inverted fishbone deceleration markings have the highest comprehensive evaluation index, γ B 1 = 0.9644.